Estudio de la cinética de osmodeshidratación aplicando vacío en aguaymanto (Physalis peruviana L.) - Chuquipoma Morales, José Daniel (2018)
We studied the effect of temperature, osmotic concentration, acidity and vacuum pressure during the osmotic dehydration of Aguaymanto (Physalis peruviana L.). A syrup/fruit ratio of 4:1 was used during 180 minutes of the process making readings every 15 minutes. The variables studied significantly influenced moisture, water activity and b*. However, the soluble solids by effect of temperature, osmotic concentration and acidity; pH by effect of temperature and osmotic concentration; Acidity index by effect of temperature and acidity; L* by temperature and osmotic concentration; a* by effect of osmotic concentration. Three mathematical models were compared to describe the kinetics of water loss and the gain of solids at different temperatures (40, 50 and 60 °C), osmotic concentration (30, 40 and 50 °Brix), acidity (0.05, 0.075 and 0.1% citric acid) and vacuum pressure (200, 300 and 400 mmHg). Two empirical models were adjusted (Azuara and Peleg) and a phenomenological model from the solution of the second law of Fick. The results indicated that the model of Peleg adjusted better than the empirical model of Azuara and that to a lesser degree the phenomenological model of Fick, corroborated with the goodness of adjustment of the relative error mean percentage (ERM %) and the coefficient determination (R2). The highest water loss of 17.97 ± 2.23 % and the highest solid gain of 42 ± 3.06 °Brix were achieved under the following conditions; Temperature 60 °C, osmotic concentration 50 °Brix, acidity 0.075% and pressure 200 mmHg.